2023
DOI: 10.3390/molecules28083551
|View full text |Cite
|
Sign up to set email alerts
|

Potential Hypoglycemic and Antilipidemic Activity of Polyphenols from Passiflora ligularis (Granadilla)

Abstract: The consumption of fruits or by-products from plants of the Passifloraceae family has been associated with multiple health and nutritional benefits, due to their phenolic compound content. Likewise, the effects of polyphenols from Camellia sinensis (green tea) have been explored and are considered a reference for different biological actions of these bioactive substances. This study compared the hypoglycemic and antilipemic activity of polyphenol-rich extracts of Passiflora ligularis Juss (passion fruit) and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
1
0
1
Order By: Relevance
“…Similar behavior was also reported for different extracts of P. edulis in diabetic rats, attributed to glycosyl flavonoids [ 51 , 52 ]. Improvements in the lipid profile have been demonstrated by P. ligularis in obese rats and is correlated with the decrease in hepatic steatosis [ 53 ]. The results of the present study are according to previous studies which demonstrated the antilipidemic activity of isoquercetin in a dependent dosage which attenuated triglycerides and cholesterol levels in diabetic mice [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar behavior was also reported for different extracts of P. edulis in diabetic rats, attributed to glycosyl flavonoids [ 51 , 52 ]. Improvements in the lipid profile have been demonstrated by P. ligularis in obese rats and is correlated with the decrease in hepatic steatosis [ 53 ]. The results of the present study are according to previous studies which demonstrated the antilipidemic activity of isoquercetin in a dependent dosage which attenuated triglycerides and cholesterol levels in diabetic mice [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…doi https://doi.org/10.21776/ub.jkptb.2023.011.03.09 1. Pendahuluan Passiflora merupakan sebuah genus tanaman rambat atau disebut juga spesies tanaman semak yang memiliki lebih dari 500 spesies di seluruh dunia [1], [2]. Berbagai penelitian melaporkan bahwa bagian tanaman Passiflora memiliki sifat anti inflamasi, antioksidan, dan anti tumor.…”
unclassified